1989
DOI: 10.1021/ed066p223
|View full text |Cite
|
Sign up to set email alerts
|

What makes chemistry difficult? Alternate perceptions

Abstract: Providing a way in which students can communicate honestly about their difficulties in chemistry can provide valuable information to the instructor about the context students impose upon their chemistry course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 0 publications
3
61
0
2
Order By: Relevance
“…Chemistry has received far less attention from educational researchers especially when compared to other domains such as physics, biology or mathematics (Anderson, 1986;Carter and Brickhouse, 1989;Kozma and Johnston, 1990;Krajcik, 1991). In general prior research indicates that an expert chemist's understanding of chemical concepts is embedded in a conceptual framework that they have developed over time through the active integration and structuring of concepts about the nature of matter and chemical change.…”
Section: Introducing the Periodic Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Chemistry has received far less attention from educational researchers especially when compared to other domains such as physics, biology or mathematics (Anderson, 1986;Carter and Brickhouse, 1989;Kozma and Johnston, 1990;Krajcik, 1991). In general prior research indicates that an expert chemist's understanding of chemical concepts is embedded in a conceptual framework that they have developed over time through the active integration and structuring of concepts about the nature of matter and chemical change.…”
Section: Introducing the Periodic Systemmentioning
confidence: 99%
“…Some indication of the potential source of the problems students faced in learning chemistry can be found in a study that probed differences between students and experts in their perception of chemistry (Carter and Brickhouse, 1989). They found that the most significant difference between experts and novices related to their beliefs about the nature of chemistry.…”
Section: Introducing the Periodic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Students themselves feel that chemistry is a difficult subject (Solomon, 1983;Carter & Brickhouse, 1989). Within chemistry the topic of chemical kinetics has been shown to be difficult for a great nximber of first year college level chemistry students.…”
Section: Introductionmentioning
confidence: 99%